Outcome of liver cancer patients with SARS‐CoV‐2 infection: An International, Multicentre, Cohort Study. (23rd June 2022) - Muñoz‐Martínez, Sergio; Sapena, Victor; Forner, Alejandro; Bruix, Jordi; Sanduzzi‐Zamparelli, Marco; Ríos, José; Bouattour, Mohamed; El‐Kassas, Mohamed; Leal, Cassia R. G.; Mocan, Tudor; Nault, Jean‐Charles; Alves, Rogerio C. P.; et al.
Abstract: Background & Aims: Information about the impact of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) in patients with liver cancer is lacking. This study characterizes the outcomes and mortality risk in this population. Methods: Multicentre retrospective, cross‐sectional, international study of liver cancer patients with SARS‐CoV‐2 infection registered between February and December 2020. Clinical data at SARS‐CoV‐2 diagnosis and outcomes were registered. Results: Two hundred fifty patients from 38 centres were included, 218 with hepatocellular carcinoma (HCC) and 32 with intrahepatic cholangiocarcinoma (iCCA). The median age was 66.5 and 64.5 years, and 84.9% and 21.9% had cirrhosis in the HCC and iCCA cohorts respectively. Patients had advanced cancer stage at SARS‐CoV‐2 diagnosis in 39.0% of the HCC and 71.9% of the iCCA patients. After a median follow‐up of 7.20 (IQR: 1.84–11.24) months, 100 (40%) patients have died, 48% of the deaths were SARS‐CoV‐2‐related. Forty (18.4%) HCC patients died within 30‐days. The death rate increase was significantly different according to the BCLC stage (6.10% [95% CI 2.24–12.74], 11.76% [95% CI 4.73–22.30], 20.69% [95% CI 11.35–31.96] and 34.52% [95% CI 17.03–52.78] for BCLC 0/A, B, C and D, respectively; p = .0017). The hazard ratio was 1.45 (95% CI 0.49–4.31; p = .5032) in BCLC‐B versus 0/A, and 3.13 (95% CI 1.29–7.62; p = .0118) in BCLC‐C versus 0/A in the competing risk Cox regression model. Nineteen out of 32 iCCA (59.4%) died, and 12 deaths were related to SARS‐CoV‐2 infection. Conclusions: This is the largest cohort of liver cancer patients infected with SARS‐CoV‐2. It characterizes the 30‐day mortality risk of SARS‐CoV‐2 infected patients with HCC during this period.